Pharmacological pain management in patients with rheumatoid arthritis: a narrative literature review - Natasha Cox; Christian D. Mallen; Ian C. Scott (BMC Medicine)
Abstract Background Pain is a major challenge for patients with rheumatoid arthritis (RA), with many people suffering chronic pain. Current RA management guidelines focus on assessing and reducing disease activity using disease-modifying anti-rheumatic drugs (DMARDs). Consequently, pain care is often suboptimal, with growing evidence that analgesics are widely prescribed to patients with RA, despite potential toxicities and limited evidence for efficacy. Our review provides an overview of pharmacological treatments for pain in patients with RA, summarising their efficacy and use. Findings Thirteen systematic reviews of drug efficacy for pain in patients with RA were included in this review. These showed moderate- to high-quality evidence from clinical trials in more contemporary time-periods (mainly 1990s/2000s for synthetic DMARDs and post-2000 for biological/targeted synthetic DMARDs) that, in patients with active RA, short-term glucocorticoids and synthetic, biologic, and targeted synthetic DMARDs have efficacy at reducing pain intensity relative to placebo. In contrast, they showed low-quality evidence from trials in more historical time-periods (mainly in the 1960s–1990s for opioids and paracetamol) that (aside from naproxen) analgesics/neuromodulators provide any improvements in pain relative to placebo, and no supportive evidence for gabapentinoids, or long-term opioids. Despite this evidence base, 21 studies of analgesic prescribing in patients with RA consistently showed substantial and sustained prescribing of analgesics, particularly opioids, with approximately one quarter and > 40% of patients receiving chronic opioid prescriptions in each year in England and North America, respectively. Whilst NSAID prescribing had fallen over time across countries, gabapentinoid prescribing in England had risen from < 1% of patients in 2004 to approximately 10% in 2020. Prescribing levels varied substantially between individual clinicians and groups of patients. Conclusions In patients with active RA, DMARDs have efficacy at reducing pain, supporting the role of treat-to-target strategies. Despite limited evidence that analgesics improve pain in patients with RA, these medicines are widely prescribed. The reasons for this are unclear. We consider that closing this evidence-to-practice gap requires qualitative research exploring the drivers of this practice, high-quality trials of analgesic efficacy in contemporary RA populations, alongside an increased focus on pain management (including pharmacological and non-pharmacological options) within RA guidelines.